PRELIMINARY STUDY OF SOUTH EAST SULAWESI LIMONITIC NICKEL ORE LEACHING IN HIDROCLHORIC ACID SOLUTION AND RECOVERY OF NICKEL FROM PREGNANT LEACH SOLUTION BY LEWATIT TP 207 ION EXCHANGE RESIN - SALLE KARURUNG , ALEX
Production of nickel from lateritic ore through pyrometallurgical route is an energy intensive process and therefore not suitable for low grade ore. For processing of the low grade lateritic ore, the technology that has been developed and widely applied in industry is hydrometallurgy process via high pressure acid leaching (HPAL). In fact, the application of HPAL process has been facing a lot of problems associated with corrosion and scaling in autoclave that increases maintenance cost. Moreover, HPAL process needs high capital cost for the equipments. The possibility of using atmospheric leaching to process lateritic ore has been investigated in which sulphuric acid is the most frequently used leaching agent. Compare to HPAL process which is selective to iron, the sulphuric acid atmospheric leaching has low selectivity to iron. This research is aimed at investigating the use of hydrochloric acid as an alternative leaching agent for atmospheric leaching in tank of lateritic nickel ore. In this research project, lateritic nickel ore sample from the province of South East Sulawesi was used. Leaching experiments have been conducted in five-neck reactor with variations of acid concentration, pulp density, temperature and addition of ferric chloride (FeCl3). The pregnant solutions were analyzed by AAS (Atomic Absorption Spectrophotometer) in order to know the extraction percentage of Ni, Fe and Mg. Leaching kinetic was approached by shrinking spherical core model. The pregnant solutions were purified by aeration and pH adjustments to selectively precipitate the iron, prior to nickel recover process by ion exchange resin. The nickel recoveries were done by passing the purified pregnant solution through a column filled with TP 207 type of the ion exchange resin from Lewatit. The feed velocity has been set at 1.5 ml per minute by using a peristaltic pump, while the solution pH was varied in the range of 2.6 to 4. To obtain nickel and iron recoveries, metals concentrations prior to and after the solutions passing through the ion exchange bed were determined. The experiment result showed that the highest percentage of nickel extraction was 91% which was obtained from the leaching test with -14+48# size fraction of limonite ore, 3M HCl at 95 oC and 10% solid. Increasing acid concentration above 3M did not significantly affect nickel extraction and even increased dissolutions of magnesium and iron. The investigation result showed that the leaching process tends to be more selective to nickel at higher pulp densities. It has also been found that the addition of ferric chloride decreased nickel and iron extractions and reversely increased magnesium extraction. From kinetic study, it has been known that the leaching process was controlled by HCl diffusion through the solid product at un-reacted core with energy activation of around 18.47 kcal. The purification of pregnant solution by aeration and pH adjustment method was found to be effective to depress the solubility of iron up to 0.1-0.2 gpl with nickel recoveries of 75 to 90%. Despite its low selectivity to iron, high recoveries of nickel in the range of 85 to 100 % were obtained from the adsorption experiments with Lewatit TP 207 ion exchange resin at pH > 3.